Peningkatan Hasil Belajar FPB dan KPK Menggunakan Pendekatan Pendidikan Matematika Realistik (PMR) di Kelas IV SDN 13 Salimpaung - Azizah, Nurul; Zainil, Melva; Lena, Mai Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to find out the improvement of learning outcomes of fourth grade students of SDN 13 Salimpaung on FPB and KPK learning by applying a realistic mathematics education approach (PMR). This study was classroom action research (CAR) conducted in 2 cycles, which each cycle consists of planning, implementation, observation and reflection. Subjects of this study were researcher, teacher, and 34 students at grade four. The results showed an increase in: a) Lesson plan in cycle I was 87 (good) and increased to96 (very good) cycle II; b) Teacher activity in cycle I was 84 (good) and increased to 92 (very good) in cycle II. While the activities of students in cycle I was 80 (good) and increased to 92 (very good) in cycle II; c) Student learning outcomes from the aspects of attitude, knowledge, and skills in the cycle I was 78,7, and increase to 89,1 in the cycle II with good criteria.Key words: Learning outcomes, FPB and KPK, PMR approach